Concurrency Control in the Problem of Automatic Substitution of the Dataflow Network Agent on Smart-M3 Platform and in the Internet of Things - S. I. Balandin; A. M. Vasilev; N. I. Kozhemyakin; D. A. Laure; I. V. Paramonov (Моделирование и анализ информационных систем, 2015)
The paper describes implementation of dataflow networks based on Smart-M3 platform for use cases related to the Internet of Things. The mechanism for automatic substitution of computational agents created on top of Smart-M3 platform is described. The paper reviews concurrency issues of the developed solution regarding Smart-M3 platform, as well as in the broader context of the Internet of Things.